Analisis Model Altman Z-Score dalam Memprediksi Potensi Kebangkrutan Perusahaan Asuransi Jiwa Syariah di Indonesia: Analysis of the Altman Z-Score Model in Predicting the Potential Bankruptcy of Sharia Life Insurance Companies in Indonesia - Ardiaprila, Cantika; Puspitasari, Novi; Sulthoni, Moch. (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2023)
This research is a qualitative study with a population of Sharia Life Insurance in Indonesia. The research sample is a Sharia Life Insurance company registered with the Financial Services Authority (OJK) for the 2017-2021 period, namely Full Sharia Life Insurance and published financial reports that have been audited, namely the company PT. Family Takaful, PT. Al-Amin, PT. Amanahjiwa Giri Artha, PT. Jasa Mitra Abadi, and PT. Indonesian family. Data obtained through OJK from the company's official website. The research data were processed using the modified Altman Z-score formula. The analysis in this study was carried out using descriptive statistics. The results of this study were taken based on the cut off value. A Z value <1.23 is declared bankrupt, a value between 1.23 and 2.9 is declared a gray area or prone to bankruptcy, and a value > 2.9 is declared not bankrupt. The results of the analysis of potential bankruptcy predictions Altman z-score that PT Takaful Keluarga, PT Amanahjiwa Giri Artha and PT Keluarga Indonesia are in the category of non-bankrupt companies. Meanwhile, PT Al-Amin is in the unsafe category or is called the gray area because Al-Amin in 2019, 2020 and 2021. The last company, namely PT Jasa Mitra Abadi, was included in the bankrupt category in 2017 showing results Z < 1.23, namely - 67.74 Furthermore, PT Jasa Mitra Abadi also entered a gray area or prone to bankruptcy from 2018 to 2021.